2x - 2 = 4x + 6
first move all the x's to one side by adding or subtracting from both sides:
2x - 2 - 2x = 4x + 6 - 2x
-2 = 2x + 6
then move all the number to the other side by adding or subtracting from both sides:
-2 - 6= 2x + 6 - 6
-8 = 2x
then divide Both sides by the x coefficient:
-8 / 2 = 2x / 2
-4 = x
ta da! x = -4
check but putting it back in original equation:
2 (-4) - 2 = 4 (-4) + 6
-8 - 2 = -16 + 6
-10 = -10
similar for the second problem:
2.6h+18= 2.4h+22
2.6h + 18 - 2.4 h = 2.4h + 22 - 2.4h
.2h + 18 = 22
.2h + 18 - 18 = 22 - 18
.2h = 4
.2h / .2 = 4 / .2
h = 20
ta da! h = 20
check:
2.6 (20) + 18 = 2.4 (20) + 22
52 +18 = 48 + 22
70 = 70
good luck
2007-01-28 13:09:29
·
answer #1
·
answered by saintcady 2
·
1⤊
0⤋
The first goal is to get the variables on the same side. It's usually best to collect them all to the side where the larger coefficient is.
2x - 2 = 4x + 6
subtract 2x from both sides and you get
-2 = 2x + 6
Now this is a one-step equation that you probably can do.
subtract 6 then divide by 2
x = - 4
The second problem is the same as the first but has decimals.
subtract 2.4 x from both sides which will result in
.2h + 18 = 22
then subtract 18 and divide by .2
h = 20
2007-01-28 21:20:27
·
answer #2
·
answered by what-about-bob 3
·
0⤊
0⤋
You need to move the terms with the variable to one side of the = sign and the terms with no variable to the other side. This is done by adding the opposite of the term you wish to move to both sides of the equation. After that, you will need to divide both sides by the number in front of the variable.
It is often easier to keep the variable positive. In the first example you would add -2x to both sides then add -6 to both sides
-2x + 2x - 2 = -2x + 4x + 6
-2 = 2x - 6
-2 + -6 = 2x + 6 + -6
-8 = 2x
-8/2 = 2x/2
-4 = xThen check to make sure it is right by replacing x with -4 in the original problem.
-8 - 2 = -16 + 6
-10 = -10 check
2007-01-28 21:06:04
·
answer #3
·
answered by hayharbr 7
·
1⤊
0⤋
2x-2=4x+6 , you subtract both side for 2x ( subtract 2x at 2x of the left side and subtract 2x at 4x of the right side) which will make the 2x from the left side get eliminated then the problem be came
-2=2x+6 , you subtract 6 from both side again , this time subtract at those two numbers -2 and 6 at both side , which will make the +6 from the right side get eliminated , then the problem become
-8=2x , then you divide both side by 2 , which will help you cancel out the 2 in front of x and leave you with 1x only , and you should get
-4=x, then your done for the 1st problem
repeat the step for the 2nd one , but use different number and i think u should try this by your own
2007-01-28 21:10:06
·
answer #4
·
answered by Kaka D LE 2
·
1⤊
0⤋
ok u put the similar terms on the same side of the = sign.
so for the fist one u would take the 4x to the other side and turn it into a -4x. and then take the 2 to the right side and turn it into a -2
u would get 2x-4x=6-2
u would end up with: -2x=4 which is x=-2
same goes for the other one. hope this helps:)
2007-01-28 21:05:57
·
answer #5
·
answered by randomdood 2
·
0⤊
0⤋
2x-2=4x+6 so 2x-4x = 6+2 -2x= 8 and x=-4
(2.6-2.4)h = 22-18 0.2h= 4 so h=20
2007-01-28 21:08:39
·
answer #6
·
answered by santmann2002 7
·
1⤊
0⤋
you have to put the x or the h on one side. Do this by subtracting or adding depending on its negation so you'll end up getting -2x=8 if you subtract 4x from both sides and add 2 from both sides. And then solve for X.......-4
2007-01-28 21:06:16
·
answer #7
·
answered by Mag1527 3
·
1⤊
0⤋
Minus 2x and six on both sides.
You get 2x= -4.
Then, divide both sides by 2 and your answer is x= -2.
The second problem is the same situation.
2007-01-28 21:10:31
·
answer #8
·
answered by T-Vol 5
·
1⤊
0⤋
2x-2= 4x+6
2x-4x = 6+2
-2x =8
x= -4
2.6h+18= 2.4h+22
2.6h-2.4h = 22-18
.2h =4
h = 20
2007-01-28 21:11:34
·
answer #9
·
answered by ironduke8159 7
·
1⤊
0⤋
1)2x-2=4x+6
Subtract 4x from both sides:
-2x-2=6
Add 2 from both sides:
-2x=8
Divide -2 from both sides:
x=-4
Check:
2(-4)-2=4(-4)+6
-8-2=-16+6
-10=-10
2)2.6h+18=2.4h+22
Subtract 2.4h from both sides:
0.2h+18=22
Subtract 18 from both sides:
0.2h=4
Divide 0.2 from both sides:
h=20
Check:
2.6(20)+18=2.4(20)+22
52+18=48+22
70=70
I hope this helps1
2007-01-28 21:19:13
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋